Piloting the Virtual PLAYshop Program: A Parent-Focused Physical Literacy Intervention for Early Childhood - Yeongho Hwang; Madison Boyd; Patti-Jean Naylor; Ryan E. Rhodes; Sam Liu; Ramiah Moldenhauer; Joshua Li; Chris Wright; E. Jean Buckler; Valerie Carson (MDPI AG, 2023)
The PLAYshop program is a parent-focused physical literacy intervention for early childhood. This single-group mixed-methods pilot study aimed to explore the feasibility of virtually delivering and assessing the PLAYshop program. The virtual PLAYshop program included a virtual workshop, resources/basic equipment, and two booster emails (3-week and 6-week follow-up). Data on 34 preschool-aged children (3-5 years) and their parents from Edmonton and Victoria, Canada, were collected via an online questionnaire, virtual assessment session, and interview at single or multiple time points (baseline, post-workshop, 2-month follow-up). Intraclass correlation coefficients (ICCs), paired t-tests, repeated measures ANOVAs, and thematic analyses were conducted. Regarding feasibility, most parents (≥94%) were satisfied/extremely satisfied with the virtual workshop and planned to continue physical literacy activities post-workshop. The virtual assessment protocol for children's fundamental movement skills (FMS; overhand throw, underhand throw, horizontal jump, hop, one-leg balance) was feasible, with high completion rates (>90%) and reliable scoring (ICC = 0.79-0.99). For positive changes in potential outcomes, a medium effect size was observed for children's hopping skills (d = 0.54), and large effect sizes were observed for several parental outcomes (partial η2 = 0.20-0.54). The findings support the feasibility and potential positive outcomes of the virtual PLAYshop program. A larger randomized controlled efficacy trial is recommended.